A Randomized FiveYear Comparative Study of Two LevonorgestrelReleasing Implant Systems: Norplant® Capsules and Jadena® Rods - Affandi, Biran; Ridwan, Rusdi S; Hoesni, R Hasan M; Tandjung, Thamrin; Ichsan, TM; Amran, Rizani; Manan, Heriyadi; Gunardi, Eka R; Pramana, Noor; Hadiyono, Suryo; Widohariadi, Widohariadi; Farid, Retno B; Taher, Mardiah (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To provide a randomized comparison between Jadena® and Norplant® in terms of efficacy and acceptability among Indonesian women. Method: This study was a phase IV, open label, randomized, multicenter study throughout Indonesia. Subjects were Indonesian adult women who were randomized to receive Jadena® or Norplant® as their contraceptive method. The subjects were recruited from 6 large cities in Indonesia, such as Medan, Palembang, Jakarta, Semarang, Surabaya, and Makassar. Result: Of 600 subjects, 301 women getting to Jadena® and 299 women to Norplant® were enrolled between August 1998 and February 1999. The mean age was 29.8 (SD 5.3) years old, ranging from 18 to 40 years old. We did not find the pregnancy during the study. Non-pregnancy probability at the end of one year was similar between Jadena® (0.920 (SD 0.016)) and Norplant® users (0.916 (SD 0.084)). The continuation rates of Jadena® at one and three-year were 95.3% and 66.8%; whereas, the continuation rates of Norplant® was 94.3% at year-1 and 70.2% at year-3. Conclusion: The new two rod levonorgestrel subdermal system (Jadena®) showed similar efficacy with the old six capsule levonorgestrel subdermal system (Norplant®) in term of birth control. Both implant systems also have similar tolerability profile. Jadena® is easier to insert and remove than Norplant®. Keywords: birth control, efficacy, implant